Historical perspective on needle development: From the past to the future. (September 2022) - Karstensen, John Gásdal; Vilmann, Peter
Abstract: With the introduction of EUS, endoscopy was no longer limited to luminal indications. However, the method was unable to distinguish malignant from benign lesions. Consequently, needles designed for tissue acquisition under EUS-guidance was designed. Initially, the needles were designed for fine needle aspiration (FNA); nevertheless, with increased requirement for the precured tissue in terms of quality and quantity, newly design needles aimed at obtaining tissue cores for histological assessment were developed. Recent studies demonstrate superiority of these fine needle biopsy needles (FNB) compared to FNA needles.